Information wars in the post-Soviet media: infodemic and means of its neutralizing - Ivanova, Iryna (2021)
The research focuses on the concepts of “infodemic”, “information war” and their modern transformations. In order to determine the theoretical basis of the work, inductive and deductive methods of analysis have been used; the method of interdisciplinary research has been involved for identifying the genesis, principles of structuring and specific characteristics of infodemic as a form of informational influence of a manipulative nature. The author’s BNA-analysis made it possible to determine the nature of information influences and the effectiveness of socially valuable performance as a measure to counteract information influences and a training method.  It has been found that the interaction of different media and social communications: PR, advertising and journalism, makes it possible to increase the impact of information waves on society; infodemic is an example of such an intense impact. The problem of determining the algorithm, nature and means of combating information intrusions of a negative nature is the basis of the presented scientific studies. A number of means of counteracting the negative impact of infodemic and other information wars on the audience have been identified. A set of anti-infodemic means and an algorithm for their usage have also been presented.